Expectations Among Patients and Health Professionals Regarding Web-Based Interventions for Depression in Primary Care: A Qualitative Study - Montero-Marín, Jesús; Prado-Abril, Javier; Botella, Cristina; Mayoral-Cleries, Fermin; Baños, Rosa; Herrera-Mercadal, Paola; Romero-Sanchiz, Pablo; Gili, Margalida; Castro, Adoración; Nogueira, Raquel; García-Campayo, Javier (JMIR Publications, 2015)
BackgroundOne-quarter of the world's population will suffer from depression symptoms at some point in their lives. Mental health services in developed countries are overburdened. Therefore, cost-effective interventions that provide mental health care solutions such as Web-based psychotherapy programs have been proposed. ObjectiveThe intent of the study was to identify expectations regarding Web-based psychotherapy for the treatment of depression in primary care among patients and health professionals that might facilitate or hinder its effects. MethodsThe expectations of untreated patients and health professionals were examined by means of interviews and focus groups. There were 43 participants (20 patients with mild and moderate levels of depression, 11 primary care physicians, and 12 managers; 22 of them for interviews and 21 for groups). A thematic content analysis from the grounded theory for interviews, and an analysis of the discursive positions of participants based on the sociological model for groups were performed. Interpretations were achieved by agreement between three independent analysts. ResultsAll participants showed a good general acceptance of Web-based psychotherapy, appreciating possible advantages and improvements. Patients, physicians, and managers shared the same conceptualization of their expectations, although highlighting different aspects. Patients focused on the need for individualized and personalized interaction, while professionals highlighted the need for the standardization of the program. Physicians were concerned with extra workload, while managers were worried about optimizing cost-effectiveness. ConclusionsExpectations of the different participants can conflict with each other. Finding a balanced position among them is needed if we are to harmoniously implement effective Web-based interventions for depression in routine clinical practice.